2021
DOI: 10.1186/s13213-021-01643-7
|View full text |Cite
|
Sign up to set email alerts
|

Multifarious functional traits of free-living rhizospheric fungi, with special reference to Aspergillus spp. isolated from North Indian soil, and their inoculation effect on plant growth

Abstract: Purpose Rhizospheric soil fungi are critical for plant and soil health. However, their multiple functional traits and impact on plant growth have not been systematically explored. Methods During this study, biochemical traits of 73 indigenous soil fungal isolates and 15 unidentified isolates related to plant growth promotion and production of extracellular enzymes were studied. Results Forty four (65.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
4
9
0
Order By: Relevance
“…For this reason, in this study, two fungal strains A. fumigatus and R. oryzae as PGPF which could be used to generate plant defiance against Fusarium wilt. In accordance with our results, previous studies reported that Aspergillus species can be used for growth promotion and control of fungal plant diseases [50][51][52][53][54]. Hung and Lee Rutgers [50] illustrated that Aspergillus spp.…”
Section: Discussionsupporting
confidence: 92%
“…For this reason, in this study, two fungal strains A. fumigatus and R. oryzae as PGPF which could be used to generate plant defiance against Fusarium wilt. In accordance with our results, previous studies reported that Aspergillus species can be used for growth promotion and control of fungal plant diseases [50][51][52][53][54]. Hung and Lee Rutgers [50] illustrated that Aspergillus spp.…”
Section: Discussionsupporting
confidence: 92%
“…The morphological and biochemical characterization of isolates, on the other hand, provided comprehensive information about the isolates (Domsch et al., 1980). All of the isolates tested positive for starch and cellulose hydrolysis tests, according to the biochemical analysis (Sharma & Shukla, 2008; Imran et al., 2021). Only PRF3 had a cellulose test result that was negative (Exhibit 7).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Sarkar and Chourasia (14) screened isolated bacteria to produce extracellular enzymes necessary for the effective degradation of organic solid waste. In order to screen fungal isolates for their multiple functional traits and impact on plant growth, Imran et al (11) evaluated 73 isolates for extracellular enzyme production. They found that 95.52%, 61.11%, 35.82% and 41.79% of isolates were positive for lipase, amylase, chitinase and cellulase, respectively.…”
Section: Morphological and Molecular Characterization Of Selected Iso...mentioning
confidence: 99%
“…They play an important role in nutrient cycling by enhancing the decomposition of residual organic matter in the soil, thereby providing nutrients to plants. However, their direct role in promoting plant growth is less explored (11,5). Cellulase and xylanase play an important role in degrading biomass rich in cellulose and hemicelluloses (36).…”
Section: Morphological and Molecular Characterization Of Selected Iso...mentioning
confidence: 99%
See 1 more Smart Citation